Efeitos de cordões de pedra em contorno na produtividade de solo litólico. - Silva, Francisco José da (1995)
Previous research demonstrated the effectiveness of contoured lines of stones in reducing slope lenghts, decreasing runoff and erosion rates, retaining sedirnents and nutrients and in decreasing the siltation of reservoirs. The dimensions of those benefits in terrns of soil productivity in semiarid regions, however, remained unknown. This study was conducted in order to determine the effects of contoured lines of stone on soil productivity as measured by crops yields on a Lithosol after thirteen years of protection by this soil and water conservation practice in Quixadá, State of Ceará, BraziI. Deterrninations of cowpea (Vigna unguiculata (L.) Wolp.) and corn (Zea mays L.) yields were accomplished on plots located immediately above the contoured lines of stones where was evident sediments deposition in layers of up to 30 cm thick and on plots distant 19 m of those lines where topsoil removal was detected through morphological, chemical and physical analisys of the soil profiles on both areas where crops were grown. Cowpea pods number per plant, grain nurnber per plant and grain weight per plant increases in deposition sites along the stone lines were 48.6%, 140.0% and 85.5%, respectively, when compared to these parameters determined in removal sites. These increases affected cowpea yield which was 85.5% greater in deposition sites, significant at the 5% level. Corn production was also affected beneficially by contoured stone lines since yield in deposition sites (1,368 Kg/ha) was 16.5% higher than in removal sites (1,174 Kg/ha) although only increases in plant height (12.3%) and cob lenght (20.7%) were significant at the 5% leveI. This conservation practice induced marked improvements in soil quality as related to increases in effective depth, parosity, available water, organic matter, N, pH, sum of bases, base saturation and cation exchange capacity, and decrease in AI content on layers whose mass amounted to 780 t/ha of precious sediments retained by the stone lines after 13 years of erosion control.